Multiple and Highly Selective Alkyne-Isonitrile C-C and C-N Couplings at Group4 Metallocenes - Altenburger, Kai; Arndt, Perdita; Becker, Lisanne; Reiss, Fabian; Burlakov, Vladimir V; Spannenberg, Anke; Baumann, Wolfgang; Rosenthal, Uwe (Chemistry : a European journal, 2016)
Reactions of the group4 metallocene alkyne complexes [Cp'2M(η2-Me3SiC2SiMe3)] [Cp'2=rac-(ebthi)=rac-1,2-ethylene-1,1'-bis(η5-tetrahydroindenyl): M=Ti, Zr, Hf; Cp'2=Cp*2 (Cp*=η5-pentamethylcyclopentadienyl): M=Zr] with 2,6-dimethylphenyl isocyanide (2-xylyl isonitrile, XyNC) were investigated. Depending on the metal, the Cp' ligand, and/or the stoichiometry, as well as the reaction temperature and time, different products were obtained. The products included simple end-on coordination compounds of XyNC in addition to those of the coupling of Me3SiC2SiMe3 with two, three, or four isonitriles to form enimine complexes, aza-metallacycloallenes, and fused heterocyclic systems, respectively. One example of the latter tricyclic compounds was subject to demetalation by using HCl. Molecular structures of the heterometallacycles were determined by X-ray crystallography. The interconversion of the products was investigated by 1HNMR spectroscopy.